A telemonitoring system for nutritional intake in patients with chronic kidney disease receiving peritoneal dialysis therapy. (June 2019) - Olivares-Gandy, Hugo J.; Domínguez-Isidro, Saúl; López-Domínguez, Eduardo; Hernández-Velázquez, Yesenia; Tapia-McClung, Horacio; Jorge de-la-Calleja,
Abstract: Patients undergoing peritoneal dialysis (PD) therapy may present complications of protein-energy wasting, which may be partially produced by inadequate nutrition management and a protein or energy deficiency in the predialytic phase. Therefore, accurate monitoring of the nutrition status during PD therapy can prevent risk conditions in patients with chronic kidney disease (CKD). In this study, we present the analysis, design, and development of a telemonitoring system for the nutritional intake of patients with CKD receiving PD therapy. The proposed system consists of a mobile web application addressed to the nutrition specialist and a native Android application aimed at patients undergoing PD. Our system optimizes nutrition administration by providing services that allow the nutritionist to monitor the patient, assign a nutrition scheme based on the patient profile, manage intake phases and send recommendations to the patient. Furthermore, the system allows the patient to record the intake data daily, receive updates on diets generated by the nutritionist and communicate with the nutritionist through a consultation module. Finally, we performed a usability assessment of our system based on a laboratory study with two users: a nutritionist and a patient undergoing peritoneal dialysis treatment. Based on the obtained results, our telemonitoring system shows a favorable opinion in terms of usability from the perspectives of the patient and nutritionist.